ANALISIS FAKTOR PENURUNAN ANGKA STUNTING DI KABUPATEN SERAM BAGIAN TIMUR - Tuanaya, Siti Rania; Sahusilawane, Aphrodite Milana; Timisela, Natelda R. (Program Studi Agribisnis Fakultas Pertanian, 2025)
Stunting is a serious health problem that impacts children's physical and cognitive development, and Indonesia still faces big challenges in reducing its prevalence. This research aims to analyze the factors that influence the reduction in stunting rates in Akijaya Village, Waisamet Village and Banggoi Pancoran Village, West Bula District, East Seram Regency, with a focus on the influence of policy, health, environment and socio-economics on parenting patterns and children's nutritional status. The research results show that the effectiveness of the Supplementary Feeding Program (PMT) has a significant impact in improving children's nutritional status, especially with educational support to parents. Apart from that, strengthening Posyandu plays an important role in monitoring children's growth and development and increasing public awareness about balanced nutrition. Socio-economic and educational factors also influence stunting rates, where families with higher levels of education tend to have a better understanding of children's nutrition. Government policies, including budget allocation and training of health cadres, have contributed to the success of the stunting reduction program. Even though the programs implemented have shown positive results, there are still challenges in terms of program sustainability, limited resources and community participation. Therefore, this research recommends increasing the budget for nutrition programs, training health cadres, and strengthening collaboration between the government, private sector and society in dealing with stunting in a sustainable manner.